The CD8 T Cell Response to Respiratory Virus Infections - Schmidt, Megan E.; Varga, Steven M. (Frontiers in Immunology, 2018)
Humans are highly susceptible to infection with respiratory viruses including respiratory syncytial virus (RSV), influenza virus, human metapneumovirus, rhinovirus, coronavirus, and parainfluenza virus. While some viruses simply cause symptoms of the common cold, many respiratory viruses induce severe bronchiolitis, pneumonia, and even death following infection. Despite the immense clinical burden, the majority of the most common pulmonary viruses lack long-lasting efficacious vaccines. Nearly all current vaccination strategies are designed to elicit broadly neutralizing antibodies, which prevent severe disease following a subsequent infection. However, the mucosal antibody response to many respiratory viruses is not long-lasting and declines with age. CD8 T cells are critical for mediating clearance following many acute viral infections in the lung. In addition, memory CD8 T cells are capable of providing protection against secondary infections. Therefore, the combined induction of virus-specific CD8 T cells and antibodies may provide optimal protective immunity. Herein, we review the current literature on CD8 T cell responses induced by respiratory virus infections. Additionally, we explore how this knowledge could be utilized in the development of future vaccines against respiratory viruses, with a special emphasis on RSV vaccination.